Advances in paediatrics in 2019: current practices and challenges in allergy, endocrinology, gastroenterology, public health, neonatology, nutrition, nephrology, neurology, respiratory diseases and rheumatic diseases - Carlo Caffarelli; Francesca Santamaria; Virginia Mirra; Ermanno Bacchini; Angelica Santoro; Sergio Bernasconi; Giovanni Corsello (BMC, 2020)
Abstract We highlight the main developments that have been published during the first semester of the last year in the Italian Journal of Pediatrics. We have carefully chosen information from numerous exciting progresses issued in the Journal in the field of allergy, endocrinology, gastroenterology, neonatology, nutrition, nephrology, neurology, public health, respiratory diseases and rheumatic diseases. The impact on the care of patients has been placed in the broader context of studies that appeared in other journals. We think that many observations can be used directly to upgrade management of patients.